Constraints on the structure of the oceanic crust of the Tamu Massif by teleseismic P-wave coda autocorrelation - Xu, Fucong; Lu, Shaoping; Cai, Chen; Chen, Han; Dong, Shaozhe (Frontiers in Earth Science, 2023)
The Tamu Massif, considered the biggest single volcano on Earth, was formed by the accumulation of enormous amounts of magma erupting to the surface. It is the largest and oldest seamount in Shatsky Rise, which is the third largest oceanic plateau on Earth. However, the formation mechanism of Tamu Massif is still controversial because evidence point to different formation hypotheses. In this paper, we applied the P-wave coda autocorrelation method and used the hydrophone waveform data acquired by the ocean bottom seismometer (OBS) deployed on Tamu Massif to constrain the oceanic crust, and these results provide new finding on the structure of the oceanic crust for Tamu Massif.We hope it can provide some implications to research the formation mechanism of Tamu Massif.These results show that some stations in Tamu Massif received reflection signals from shallower depths that are nearly parallel to the seafloor. We infer that in the shallow oceanic crust, there is a layer composed of alternating eruptions of dense, higher velocity massive lava and sparse, lower velocity pillow lava flows, which have less density and lower velocity compared to the lower oceanic crust, with a strong acoustic impedance contrasts between them and thus able to generate a reflection signal, which is observed in our autocorrelation results.